ANALISIS KONTRIBUSI MICE TERHADAP PENYERAPAN TENAGA KERJA DAN KUNJUNGAN WISATAWAN DI DAERAH ISTIMEWA YOGYAKARTA - Rosalina Nur Annisa; Dyah Wahyuning Tyas (Kepariwisataan: Jurnal Ilmiah, 2020)
This study aims to analyze the development of MICE tourism and its contribution to employment absorption in the tourism sector and tourist visits in the Special Region of Yogyakarta. MICE activities (Meetings, Incentives, Conventions, and Exhibitions) held in an area may contribute to various sectors. However, the implementation of MICE activities in an area has not yet been clearly measured for its contribution to employment absorption or number of tourist visits. This research sample uses purposive sampling technique, using primary data and secondary data. Primary data in the form of in-depth interviews and questionnaires. While secondary data in the form of data on the number of MICE, labor in the tourism sector, and tourist visits in 2014 - 2018. The analytical method used in this study is quantitative and qualitative SWOT (Strength, Weakness, Opportunities, and Threat) and is supported by descriptive statistics for strengthen analysis. The results showed the development of MICE tourism in DIY over a period of 5 years (2014-2018) had increased. MICE has grown a lot in Sleman Regency and Yogyakarta City, due to the factor of accommodation facilities, location close to tourist destinations and airports. MICE has a contribution to employment absorption seen from the positive quadrant sign between strength and weakness of 144.96. In addition, MICE also contributes to tourist visits as seen from the positive quadrant sign of 119.03.Keywords: MICE, employment absorption, tourist visit.